2017
DOI: 10.1016/j.jacc.2017.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rosuvastatin in Children With Homozygous Familial Hypercholesterolemia and Association With Underlying Genetic Mutations

Abstract: This first-ever pediatric HoFH statin trial demonstrated safe and effective LDL-C reduction with rosuvastatin 20 mg alone or added to ezetimibe and/or apheresis. The LDL-C response in children and adults was related to underlying genetic mutations. (A Study to Evaluate the Efficacy and Safety of Rosuvastatin in Children and Adolescents With Homozygous Familial Hypercholesterolemia [HYDRA]; NCT02226198).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…10,38 Moreover, the effectiveness of LA in our study is well emphasized by an incidence of CVD (22.2%) and death (16.7%) in the Roman cohort, which is more favorable than other published studies from Europe and South Africa 1,14,[22][23][24] initiated as early as possible. The first ever pediatric randomized trial with hoFH patients was recently published, 39 demonstrating safe and effective use of Rosuvastatin 20 mg (6 weeks crossover), alone or in conjunction with ezetimibe and/or LA. However, longer-term efficacy and safety data are required, particularly in a condition such as hoFH where lifetime therapy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…10,38 Moreover, the effectiveness of LA in our study is well emphasized by an incidence of CVD (22.2%) and death (16.7%) in the Roman cohort, which is more favorable than other published studies from Europe and South Africa 1,14,[22][23][24] initiated as early as possible. The first ever pediatric randomized trial with hoFH patients was recently published, 39 demonstrating safe and effective use of Rosuvastatin 20 mg (6 weeks crossover), alone or in conjunction with ezetimibe and/or LA. However, longer-term efficacy and safety data are required, particularly in a condition such as hoFH where lifetime therapy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In all trials studying efficacy and/or safety, children enrolled were generally 8 years old and above, except for some studies that lowered the age range to reach 4 year olds for simvastatin, 21 5 years old for atorvastatin, 22 and 6 year olds for rosuvastatin, 3 atorvastatin, 4 and pitavastatin. 23 All of these studies had not reported any safety issues or discontinuations, and if present, they were not related to any adverse side effect encountered.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 This would make it difficult somehow for distinctive diagnosis. Fortunately, familial hypercholesterolemia (FH) (homozygous subtype is more aggressive and dangerous but less prevalent than the heterozygous subtype with 1/300,000 to 1/1,000,000 and 1/250 respective ratios 3,4 ) is easily detected both clinically and by blood tests, where average untreated low-density lipoprotein cholesterol (LDL-C) in heterozygous and homozygous subtypes is 140 mg/dL and > 500 mg/dL, respectively, excluding secondary causes of dyslipidemia for the patients' diagnosis. 5 Cardiovascular disease (CVD) is a devastating disease of rapidly increasing prevalence nowadays, whereby it affects 41.5% of the U.S. population, among which 7% are suffering from coronary heart disease where dyslipidemia is one of its main causes.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations in one patient suggest that statins could be a promising treatment for plantar keratoderma and associated pain in PC. The long‐term use of statins, and rosuvastatin in particular, has been reported to be safe in familial hypercholesterolaemia, and they do not demonstrate a reduction in efficacy over time . It is possible that statins could effectively alleviate the main symptoms of PC that impact patients’ quality of life but the efficacy and long‐term safety of statin use in the treatment of PC needs to be demonstrated in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%